Non‐alkylating agents‐induced gonadotoxicity in pre‐pubertal males: Insights on the clinical and pre‐clinical front - Sruthi Sriram; Tiago Macedo; Annelies Mavinkurve‐Groothuis; Marianne van deWetering; Leendert H. J. Looijenga (Wiley, 2024)
Abstract Whilst chemotherapy regimens have proven to be more successful for pediatric cancer patients over the years, their influence on long‐term side effects is relatively poorly understood. One of the possible targets is the gonads, with gonadotoxic agents representing those that threaten the patient's ability to have children post surviving the primary disease treatment. Many risk stratification guidelines have categorized these agents based on the severity of their effect on the pre‐pubertal testis. While the consensus is that those agents factored with a cyclophosphamide equivalent dosage pose the highest threat to fertility (e.g. alkylating agents), other agents might still contribute to a reduced testis function; especially in the case of combination therapies. Besides, it is important to note that studies deciphering the effect of other non‐alkylating agents on the pre‐pubertal testis lack standardized conclusions for clinically relevant outcomes. This makes it imperative to ensure the knowledge gap is addressed between the clinic and pre‐clinic to understand potential gonadotoxic effects, ultimately leading to improved patient care. Therefore, this review will summarize the key findings in understanding the gonadotoxic effects of the most commonly researched non‐alkylating agents: vincristine, etoposide, doxorubicin, and imatinib on the pre‐pubertal testis.